Chemical chaperone ameliorates pathological protein aggregation in plectin-deficient muscle - Winter, Lilli; Staszewska, Ilona; Mihailovska, Eva; Fischer, Irmgard; Goldmann, Wolfgang; Schröder, Rolf; Wiche, Gerhard (Journal of Clinical Investigation, 2014)
The ubiquitously expressed multifunctional cytolinker protein plectin is essential for muscle fiber integrity and myofiber cytoarchitecture. Patients suffering from plectinopathy-associated epidermolysis bullosa simplex with muscular dystrophy (EBS-MD) and mice lacking plectin in skeletal muscle display pathological desmin-positive protein aggregation and misalignment of Z-disks, which are hallmarks of myofibrillar myopathies (MFMs). Here, we developed immortalized murine myoblast cell lines to examine the pathogenesis of plectinopathies at the molecular and single cell level. Plectin-deficient myotubes, derived from myoblasts, were fully functional and mirrored the pathological features of EBS-MD myofibers, including the presence of desmin-positive protein aggregates and a concurrent disarrangement of the myofibrillar apparatus. Using this cell model, we demonstrated that plectin deficiency leads to increased intermediate filament network and sarcomere dynamics, marked upregulation of HSPs, and reduced myotube resilience following mechanical stretch. Currently, no specific therapy or treatment is available to improve plectin-related or other forms of MFMs; therefore, we assessed the therapeutic potential of chemical chaperones to relieve plectinopathies. Treatment with 4-phenylbutyrate resulted in remarkable amelioration of the pathological phenotypes in plectin-deficient myotubes as well as in plectin-deficient mice. Together, these data demonstrate the biological relevance of the MFM cell model and suggest that this model has potential use for the development of therapeutic approaches for EBS-MD.
EVALuna2:7203